Sistema de bioimpressão com cabeçote adaptável para impressoras 3d Fused Deposition Modeling (FDM) - Alves, Tamires Pereira (2023)
3D bioprinting is a technology that simultaneously combines living cells and biomaterials through a computer-aided manufacturing process to produce a variety of iological constructs for applications in precision medicine, drug and cosmetic development, model making for study and tissue eplacement. The bioprinting of skin tissue is an alternative for replacing tissues damaged by accidents, burns or serious wounds, offering the possibility of greater control over the model to be transplante and individualization to meet each need. The high costs of acquiring and maintaining specific equipment are a barrier to popularizing the technology. The aim of this project is to develop a bioprinting system with an adaptable head for 3D printers that use Fused Deposition Modeling (FDM) technology to manufacture biologically active skin substitutes. The system will promote the modification of small 3D printers by replacing their traditional head, transforming them into 3D bioprinters that will use the extrusion bioprinting technique, enabling the manufacture of tissues with the required shape and dimensions. The proposed product is characterized by a replacement head, suitable for the technology, and a structure for stabilizing the deposition platform. Its differentials are the possibility of adapting it to different models of benchtop 3D printers, ease of assembly and operation, and the fact that it is a solution with lower development, manufacturing and assembly costs